2018
DOI: 10.3390/ma11101814
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electrochemical Properties of Gel Polymer Electrolyte with Hybrid Copolymer of Organic Palygorskite and Methyl Methacrylate

Abstract: Gel polymer electrolyte (GPE) is widely considered as a promising safe lithium-ion battery material compared to conventional organic liquid electrolyte, which is linked to a greater risk of corrosive liquid leakage, spontaneous combustion, and explosion. GPE contains polymers, lithium salts, and liquid electrolyte, and inorganic nanoparticles are often used as fillers to improve electrochemical performance. However, such composite polymer electrolytes are usually prepared by means of blending, which can impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…The p(OPal‐MMA) was prepared according to the previous study . The preparation process of p(OPal‐MMA)@CPM separator is shown in Figure .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The p(OPal‐MMA) was prepared according to the previous study . The preparation process of p(OPal‐MMA)@CPM separator is shown in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…However, most of the existing Pal/polymer composites are prepared by the method of physically blending, and the properties of the prepared composites are limited by the compatibility of the polymer and Pal. In our previous study, a hybrid copolymers poly(organic Pal‐ co ‐methyl methacrylate) [p(OPal‐MMA)] were prepared and the p(OPal‐MMA) was a net shaped microporous structure and the ionic conductivity of the p(OPal‐MMA) gel electrolyte was 2.94 × 10 −3 S cm −1 at room temperature (25 °C).…”
Section: Introductionmentioning
confidence: 99%
“…One of the main problems in the use of an organic solvent electrolyte is its low term stability, which is caused by its high‐temperature instability, low boiling point, easy evaporation, leakage, and difficulty of sealing. To overcome this problem, a lot of compounds have been used to replace organic‐based electrolytes with solid or quasisolid‐state electrolytes including inorganic p ‐type semiconductors, polymer gel electrolytes, and organic hole transport materials …”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16] One of the main problems in the use of an organic solvent electrolyte is its low term stability, which is caused by its hightemperature instability, low boiling point, easy evaporation, leakage, and difficulty of sealing. To overcome this problem, a lot of compounds have been used to replace organic-based electrolytes with solid or quasisolid-state electrolytes including inorganic p-type semiconductors, 17 polymer gel electrolytes, [18][19][20][21][22] and organic hole transport materials. 23,24 Among the electrolytes ever used, gel-state polymer electrolytes have gained interest because of their high ionic conductivity, excellent interfacial contact property, and long stability at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [16] found that the Pal can enhance prominently thermal stability and mechanical property of PMMA after Pal was modified by 2,4-tolylene diisocyanate. In the previous study [17], a inorganic-organic hybrid polymer (poly(organic Pal-co-methyl methacrylate), p(OPal-MMA)) was prepared from MMA and organic Pal. The polymer has many net shaped microporou structures and the ionic conductivity of the hybrid polymer-based GPE was 2.94 × 10 −3 S/cm.…”
Section: Introductionmentioning
confidence: 99%